THE WHAT’S THE MATTER? THE DILEMMA OF LANGUAGE CHOICE BETWEEN INDONESIAN AND ENGLISH IN EFL CLASSROOMS - Putri Kurniawan Aprilia (UHN IGB Sugriwa Denpasar, 2026)
In recent years, the use of the first language (L1), Indonesian, in English as a Foreign Language (EFL) classroom has become a topic of increasing debate. This research explores the considerations that influence teachers’ use of Indonesian as well as the difficulties encountered in its application. Adopting a qualitative case study design, the study involved five Indonesian EFL teachers in Malang who were deliberately selected based on their professional experience and the levels at which they teach. Data were collected through semi-structured interviews and classroom observations and were analyzed using thematic analysis. The findings indicate that teachers deliberately incorporate Indonesian to support student comprehension, clarify instructional content, and enhance learners’ confidence. However, challenges emerge when excessive reliance on Indonesian limits students’ exposure to English and restricts the development of autonomous language skills. Teachers therefore must carefully balance the use of L1 and L2, ensuring that Indonesian functions as a facilitative tool rather than a substitute for English. The study underscores the importance of ongoing evaluation, teacher development, and supportive learning environments to enhance English proficiency while optimizing L1 use.